A Token-Passing Variable Buffer Model For A Double-Layered Hierarchical WDM All-Optical Network - Tee, Elok Robert; Ramani, A.K.; Selvakennedy, S. (Malaysian Journal of Computer Science, 1997)
Presents a hierarchical all-optical network, employing wavelength division multiplexing for multiple channel transmission. A double-layered network with multiple sub-network implementation which provides for spatial wavelength reuse is considered. The piggybacked tokenpassing medium access protocol as a fair and noncontentious access scheme is studied for performance. The average delay in getting access to the network medium is determined from the semi-Markov process. The performance of the protocol model design with variable buffer sizes of the transmitter is analysed. It is shown from the double-layered hierarchical network that alternative route for data transmission can be implemented to improve on performance.